Let S Play: Toward an Effective Approach to Assess Online Inquiry Competences at School Level - Joglar-Campos, C; Silva-Quiroz, J; Ponce-Arias, H; Kohler-Casasempere, J; Gonzalez-Ibanez, R; Gacitua-Vasquez, D; Proaño-Rios, V; Chourio-Acevedo, L (IEEE Computer Society, 2021)
In the current information age, information literacy is crucial to face the overwhelming amount of content on the Web. Specifically, knowing and being capable of searching for information, assessing information sources,identifying main ideas, and using information to solve problems, constitute a set of fundamental competences for online inquiry. At school level, this set of competences, which canbe referred to as online inquiry competences (OIC), are necessary not only to deal with school assignments, but also with daily life where exposure to web content is quite common even at an early age. Given its importance, a major problem is how to effectively assess students OIC. To address this problem, in this article we first offer a review and comparison of different approaches to tackle OIC assessment and then, based on the results of our review, we introduce the Trivia and Adventure serious games platforms, which are designed to engage students and support the assessment of OIC at school level. These games are unique because of their open source orientation, innovative approach to assess OIC through behavioral data, user-centered design, flexibility, and potential to be used by bothresearchers and teachers, who will be empowered to create their own studies and assessments. © 2021 IEEE.